‘We’re All Mad Here’: Alienation, Madness, and Crafting Tom Waits - Nadia López-Peláez Akalay (Interlitteraria)
Tom Waits, through his poetry, his poetic and public personae, has become the father of the desperate failures of society, those who lay down and fill the background with disillusionment. No-direction-homers flock together and become the majority of Waits’ main characters. As an artist, he gives a voice and a name to those who, otherwise, would remain invisible, endowing them with corporeality. Waits, through the projection of his public persona, illumines the lives of the weak, who strive to survive in a world that has always fed upon those below. There is something honourable about the people who struggle the most, trying to find their path in the darkest of places, and Waits, through his career as an entertainer, has always prioritised his respect for these people, praising their many faults and poor decisions, merging them with the tormented collective and thus becoming one with their sadness and horror.